To the question about the problems of socialization of adolescents in a multicultural environment - Asylbekova, L. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This article examines the social, economic, demographic, environmental issues slew of negative trends of personality formation in adolescence. Of particular concern are the increased anxiety and spiritual disorientation adolescents increase their cruelty, aggressiveness, potential conflict. The results of psychological studies show that for solving interpersonal conflicts, they need psychological support.
Keywords: adolescents; anxiety; conflict; adaptation; compromise; cooperation